2018
DOI: 10.3390/su10072266
|View full text |Cite
|
Sign up to set email alerts
|

Gaps between Awareness and Activities on Green Construction in China: A Perspective of On-Site Personnel

Abstract: On-site construction stage has been considered as the key in practicing the view of green construction. Moreover, the unity of awareness and actions of on-site contractors on green construction plays a conclusive role through the implementation of green principles on the construction site. This study aims to investigate the awareness on green construction and to identify the gaps between the awareness and activities in adopting green specifications from the perspective of on-site personnel. A questionnaire sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Chang et al stated that the awareness of construction companies in China on sustainable development remains insufficient, and whether companies are performing sustainably is often ignored [54]. Through a questionnaire survey completed by on-site personnel, Zhou et al identified the gaps between awareness and actual behaviors in the adoption of sustainable construction, and sustainable practices need to be popularized to a great extent, which reflects the necessity of our research [60].…”
Section: Factors Related To Sustainable Behaviors In Pti Projectsmentioning
confidence: 99%
“…Chang et al stated that the awareness of construction companies in China on sustainable development remains insufficient, and whether companies are performing sustainably is often ignored [54]. Through a questionnaire survey completed by on-site personnel, Zhou et al identified the gaps between awareness and actual behaviors in the adoption of sustainable construction, and sustainable practices need to be popularized to a great extent, which reflects the necessity of our research [60].…”
Section: Factors Related To Sustainable Behaviors In Pti Projectsmentioning
confidence: 99%
“…The awareness in the study was higher in comparison to Alsanad [38] who had 63 percent awareness. However, awareness of GBRTS did not translate to high utilization, and this is supported by Zhou et al [39] who showed that the level of awareness on a certain green requirement is higher than the performance. The correlation between awareness and utilization was statistically significant (p = 0.005) and this correlation has been supported by Toronto green development standard (2006), which stated that public awareness about the green building was an important component in increasing the demand for green buildings.…”
Section: Resultsmentioning
confidence: 94%
“…Djokoto et al [24] found that a demand shortage for green buildings, a lack of strategy to promote green construction, higher costs, low awareness of green technologies, and poor government support were important factors. An interesting finding from Zhou et al [25] was that although respondents agreed to involve green principles in construction at a high level, the level of adoption was much lower than that of green awareness. Apart from the these barriers, long pay back periods and a reliance on traditional practice are also identified as the most significant barriers, according to Wang [26].…”
Section: Barriers To Gcmentioning
confidence: 99%